Orientalism, modernization & Islamic architecture - Omer, Spahic (UNISSA Press, 2023)
This book is about the theory of Islamic architecture and some of its recent history. It addresses the subject matter through the lens of the perpetuity and prevalence of mosque architecture, Orientalism as the source of a great many misconceptions about Islamic architecture, and modernization, as well as westernization, as a necropolis where Islamic architecture was formally buried and forsaken. The book has four chapters, namely “Is Islamic architecture synonymous with mosque architecture?”, “Misconceptions about Islamic architecture: the role of Richard Francis Burton”, “John Lewis Burckhardt’s account of architecture in Jeddah, Makkah and Madinah”, and “The impact of modernization on Islamic architecture”. The first chapter is intended to add a new dimension to the existing discourses on Islamic architecture. It traces and relates most of the genesis and evolution of Islamic architecture to the genesis and evolution of mosque institution and its own architectural vocabulary. Indeed, almost all aspects of Islamic architecture are viewed through the prism of mosque architecture, originating from it – directly or indirectly - and basing its legitimacy on the legitimacy and acceptance of the latter. A series of sensible questions, therefore, can be asked: is Islamic architecture synonymous with mosque architecture? Can there be Islamic architecture unrelated to mosque architecture? What exactly is the architectural relationship between the mosque as an institution and the rest of religious and secular private as well as institutional buildings? The content of the chapter sheds some light on those concerns and their many conceptual and practical ramifications. The second chapter discusses the main aspects of Richard Francis Burton’s perceptions and assessments of Islamic architecture especially in Egypt. The chapter aims to put the man’s observations into perspective; to reveal how much Orientalism- and the West-centric the narratives and systems of thought about Islamic architecture still are; to allude to the ways some perennial misconceptions relating to Islamic architecture are to be done away with; and to suggest approaches for the revival of authentic Islamic architecture at the planes of philosophy, theory and practice. The chapter deals with the context of Burton’s views; an interplay of scholarship, individualism and imperialism within Burton’s personality; architecture as the highest expression of a people’s artistic feeling; the allegation that Islamic architectural is plagiarized; and the relationship between bogus modernization and Islamic architecture. At the end, a comparison between Burton and Edward William Lane is also given. The third chapter analyses John Lewis Burckhardt’s views of Islamic architecture in Jeddah, Makkah and Madinah. His views are at once comprehensive and revealing, and his perspective - that of a European non-Muslim and Orientalist who secretly performed the pilgrimage – atypical and intriguing. The following issues are concentrated on: scholarship and fairness; battling misconceptions; private domestic versus public institutional architecture; architecture and ideology; and the relationship between indigeneity, cosmopolitanism and architecture. The fourth chapter discusses the modernization (westernization) attempts in the heart of the Muslim world during the 18th, 19th and 20th centuries and how much pressure such attempts have applied on the moral fibre of Islamic society and on the integrity of its civilizational outlook. Owing to the profound meaning and universal character of Islamic architecture, the same pressure as well has been applied on it, both as a system of thought and a world of physical manifestations as well as indexes. The chapter is about how modernization was responsible for side-lining and incapacitating Islamic architecture. The focus is on Ottoman Turks and Egypt as two main representatives of Islamdom. The chapter deals with these themes: the root cause of Muslim decline; Muslims and the dilemma of modernization; the impact of modernization on architectural function; and the impact of modernization on architectural form.